A prospective randomized study comparing the efficacy between povidone-iodine gargling and benzydamine hydrochloride for mucositis prevention in head and neck cancer patients receiving concurrent chemoradiotherapy. Issue 4 (April 2023) - Kannarunimit, Danita; Chotirut, Attapol; Prayongrat, Anussara; Pakvisal, Nussara; Sitthideatphaiboon, Piyada; Lertbutsayanukul, Chawalit; Kitpanit, Sarin; Chakkabat, Chakkapong; Vinayanuwattikun, Chanida
Abstract: Background: Concurrent chemoradiation (CCRT) has been the standard treatment for organ preservation or locally advanced head and neck cancer (LAHNC). Radiation-induced oral mucositis (RIOM) is an important treatment-limiting toxicity. Benzydamine hydrochloride was recommended to prevent oral mucositis. Povidone-iodine had also been adopted to use as an oral rinse to prevent mucositis. Objective: This study compared the efficacy between benzydamine hydrochloride and 0.1% povidone-iodine to prevent RIOM in HNC patients who received concurrent chemoradiotherapy. Methods: We conducted a randomized control study in HNC patients receiving CCRT with curative intent. The stratification factors were primary site of disease, treatment modality, chemotherapy regimen, and schedule. The primary outcome was RIOM assessed by Oral Mucositis Assessment Scale (OMAS). Secondary outcomes included RIOM assessed by NCI-CTCAE, use of analgesic, antibiotics and anti-fungal drugs, hospitalization, and participant satisfaction. Results: There were 83 participants recruited for this study with 71 completing the trial. Demographic characteristics were well-balanced between both arms. The univariate regression analysis revealed that povidone-iodine correlated with less RIOM compared to benzydamine hydrochloride (coefficient −2.25, 95% CI -4.37 to −0.012, p -value 0.03). The incidence of grade III-IV CTCAE RIOM during the study period was 51.4% with benzydamine hydrochloride compared to 26.5% with 0.1% povidone iodine ( p -value 0.032). The peak incidence of grade III-IV CTCAE RIOM occurred in the 7th week of treatment (40.5% vs. 11.8%, p -value 0.01). This indicated the efficacy of povidone-iodine to prevent severe RIOM which usually most severity in the last week of CCRT treatment. The multivariate analysis revealed that the CCRT setting (definitive vs. adjuvant) and gargling agents (povidone-iodine vs. benzydamine hydrochloride were the factors associated with RIOM. Conclusion: This study demonstrated higher efficacy of 0.1% povidone-iodine gargle than benzydamine hydrochloride in mucositis prevention.